Strategi Komunikasi Pemasaran Produk Naturaworld Dalam Meningkatkan Brand Awareness Di Wilayah Babelan Bekasi - Wafa Auril Widad (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Abstract.The current business development is increasingly rapid and spread to all circles, the increase in the business world is also followed by increasing competition between entrepreneurs in selling the products offered. Inrunning a business, one must be able to use the right marketing communication strategy so that they areable to compete with other entrepreneurs. This study aims to determine and analyze the marketingcommunication strategy of NaturaWorld products in increasing brand awareness. The research method usedis descriptive qualitative with a case study on the NaturaWorld brand located in Babelan, Bekasi. Data werecollected through indepth interviews with NaturaWorld members and direct observation of marketing activitiescarried out. The results oh the study shot that the NaturaWorld brand uses a Multi-Level Marketing (MLM) system and marketing communicatiob strategy, including using a promotion mix such as advertising, sales promotions, public relations, personal selling, and direct marketing. This strategy has proven effective inincreasing brand awareness, the NaturaWorld brand has implemented 5 communication strategyimpelentation processes in increasing brand awareness. NaturaWorld members in the Babelan area, Bekasiare every concerned about the program to increase brand awareness from various aspects, ranging fromactive promotions by networks (social media, live demos) to attracting consumer interest throught variousevents and programs (events, social gatherings, webinars). from these are different forms of methods toincrease brand awareness.Keywords: Product Quality, Service Quality, Customer Satisfaction